DEVELOPMENT OF QUALITY CONTROL SAMPLE TO ASSESS SPECIFIC ACTIVITY OF ANTI-RABIES IMMUNOGLOBULIN OBTAINED FROM EQUINE BLOOD SERUM - E. G. Abramova; O. A. Lobovikova; I. V. Shul’gina; A. V. Komissarov; L. V. Savitskaya; S. V. Generalov; M. V. Galkina; Yu. K. Gavrilova; A. V. Kochkin; A. K. Nikiforov (Разработка и регистрация лекарственных средств, 2019)
The paper contains the data on the development of quality control sample (QCS) for determination of specific activity of heterologous anti-rabies immunoglobulin in neutralization test on white mice. Given are the results on QCS attestation in reference to international standard samples of human immunoglobulin against rabies. The quality control sample is put on the register of QCSs approved for application in experimental-production subdivisions and in the department of biological and technical control. It is deployed for final quality control of anti-rabies immunoglobulin preparation in commercial batches.